2006
DOI: 10.1086/498241
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Aspects of Gravitational Lensing in TeVeS

Abstract: Since Bekenstein's creation of his tensor-vector-scalar theory (TeVeS), the modified Newtonian dynamics (MOND) paradigm has been redeemed from the embarrassment of lacking a relativistic version. One primary success of TeVeS is that it provides an enhancement of gravitational lensing, which could not be achieved by other MOND theories. Following Bekenstein's work, we investigate the phenomena of gravitational lensing including deflection angles, lens equations, and time delay. We find that the deflection angle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 56 publications
1
64
0
Order By: Relevance
“…Nonetheless, Mortlock & Turner (2001) showed that for a typical elliptical galaxy, the thin-lens approximation holds; the deflection angles are the same as the GR predictions in the inner parts (where the projected distances are < ∼ 2 kpc) and approach an asymptotic value in the outer parts. Chiu et al (2006) found qualitatively similar trends for the deflection angles in a relativistic formulation of MOND by Bekenstein (2004;the tensorvector-scalar theory). Therefore, modelling the satellite galaxy in MOND can be seen as modelling the satellite galaxy in GR with a different deflection angle field, or equivalently, a different mass radial profile.…”
Section: Implications For Modified Newtonian Dynamicsmentioning
confidence: 52%
“…Nonetheless, Mortlock & Turner (2001) showed that for a typical elliptical galaxy, the thin-lens approximation holds; the deflection angles are the same as the GR predictions in the inner parts (where the projected distances are < ∼ 2 kpc) and approach an asymptotic value in the outer parts. Chiu et al (2006) found qualitatively similar trends for the deflection angles in a relativistic formulation of MOND by Bekenstein (2004;the tensorvector-scalar theory). Therefore, modelling the satellite galaxy in MOND can be seen as modelling the satellite galaxy in GR with a different deflection angle field, or equivalently, a different mass radial profile.…”
Section: Implications For Modified Newtonian Dynamicsmentioning
confidence: 52%
“…The angle of deflection has the same formulation in TeVe S as in GR but using MONDian gravitational potential instead (see, e.g., Chiu, Ko & Tian (2006); Tian et al (2013) for details). For other relativistic MOND theories, such as GEA (Zlosnik et al 2007) and BIMOND (Milgrom 2009), gravitational lensing result is the same as in Chiu, Ko & Tian (2006) for spherical symmetry case. Thus, one may expect the mass discrepancy in relativistic MOND will have the same trend as in non-relativistic MOND.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing with initial mass function (IMF), MOND can explain this small discrepancy without dark matter (Chen & Zhao 2006;Chiu, Ko & Tian 2006;Chiu et al 2011;Sanders & Land 2008;Sanders 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While the difficulty has been reported in explaining gravitational lensing of colliding galaxy clusters 1E0657-56 in modified gravities [3]. Evolution of the universe and cosmological perturbation have also been studied in [4,5,6]. These results tell us that TeVeS can explain the observed spectrum of the spatial distribution of galaxies and of the cosmic microwave radiation without dark matter if we include the contributions by neutrinos and the cosmological constant.…”
Section: Introductionmentioning
confidence: 91%